2012
DOI: 10.1002/syn.21551
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5‐HT2A receptor and α2‐adrenoceptor blockade in the asenapine‐induced elevation of prefrontal cortical monoamine outflow

Abstract: The psychotropic drug asenapine is approved for the treatment of schizophrenia and manic or mixed episodes associated with bipolar I disorder. Asenapine exhibits higher affinity for several 5-HT receptors and α(2)-adrenoceptors than for D(2) receptors. Noteworthy, blockage of both the 5-HT(2A) and α(2)-adrenergic receptors has been shown to enhance prefrontal dopamine release induced by D(2) receptor antagonists. Previous results show that asenapine, both systemically and locally, increases dopamine, noradrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 338 publications
2
19
0
Order By: Relevance
“…Interestingly, acute mirtazapine administration had this same effect (0.5 mg/kg; Haddjeri et al, 1996), while long-term mirtazapine administration did not occupy postsynaptic α 2 -adrenoceptors to a significant extent (Haddjeri et al, 1998a). In contrast to this latter result, sustained asenapine administration reduced the inhibitory response of iontophoretically applied NE, indicating that postsynaptic α 2 -adrenoceptors were blocked by asenapine -in line with a previous report (Frånberg et al, 2012). Importantly, this blockade was incomplete since acute idazoxan administration reduced the neural response to NE application even further ( Figure 4D).…”
Section: Effect Of Asenapine On the Ne Systemsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, acute mirtazapine administration had this same effect (0.5 mg/kg; Haddjeri et al, 1996), while long-term mirtazapine administration did not occupy postsynaptic α 2 -adrenoceptors to a significant extent (Haddjeri et al, 1998a). In contrast to this latter result, sustained asenapine administration reduced the inhibitory response of iontophoretically applied NE, indicating that postsynaptic α 2 -adrenoceptors were blocked by asenapine -in line with a previous report (Frånberg et al, 2012). Importantly, this blockade was incomplete since acute idazoxan administration reduced the neural response to NE application even further ( Figure 4D).…”
Section: Effect Of Asenapine On the Ne Systemsupporting
confidence: 88%
“…Two-day and 21-day administration of asenapine almost completely blocked the effect of DOI, demonstrating potent in vivo antagonism at 5-HT 2A receptors by asenapine (see Figure 1D). In line with this finding, previous reports showed that acute asenapine administration reversed the inhibitory effect of DOI on LC NE neurons, and that local application of asenapine prevented prefrontal DOI-induced elevations in 5-HT, DA and NE (Frånberg et al, 2012;Ghanbari et al, 2009). Thus, the current observations support potent antagonistic properties of asenapine on 5-HT 2A receptors, a common pharmacological property of atypical antipsychotics that could be clinically relevant in adjunct to treatment of mood disorders (Blier and Szabo, 2005).…”
Section: Effect Of Asenapine On 5-ht 2a Receptorssupporting
confidence: 85%
See 1 more Smart Citation
“…28,29) The hallucinogenic 5-HT 2A/2C agonist 4-iodo-2,5-dimethoxyamphetamine indirectly increases extracellular 5-HT release in the rat medial prefrontal cortex by stimulating glutamate release. 30) Most of the subjective effects of psilocybin are blocked by pretreatment with the 5-HT 2A/2C antagonist ketanserin, indicating that the hallucinogenic effects of psilocybin are mediated primarily by actions at the 5-HT 2A receptor. 14,15,31) We hypothesize that psilocin increases extracellular 5-HT levels through 5-HT 2A receptor activation in the mesocortical pathway.…”
Section: Discussionmentioning
confidence: 97%
“…However, their affinities for the α 2 -adrenergic receptor are different, since PAL has a higher affinity than RIS for this receptor [18]. Animal studies have shown that blockage of α 2 -adrenergic receptors greatly affects the release of dopamine and noradrenaline from the medial prefrontal cortex [32]. It has also been shown that noradrenaline is related to motivation and vigilance [33].…”
Section: Discussionmentioning
confidence: 99%